Analisis Pengaruh Tingkat Kualitas Pelayanan Jasa Puskesmas terhadap Kepuasan Pasien (Studi pada Puskesmas Pagar Dewa Lampung Barat) - Patmarina, Hepiana; Prayoga, Dandy (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
At PuskesmasPagar Dewa, West Lampung, continuous efforts have been made to improve the quality of healthcare services in order to meet the needs and expectations of the community. However, various patient complaints still persist, particularly regarding complex and convoluted service procedures, long waiting times before receiving treatment, inadequate physical facilities, as well as staff attitudes that are sometimes unresponsive and lack effective communication. These conditions have created a clear gap between patients’ expectations of ideal service and the reality they experience on the ground. This study aims to analyze the effect of service quality on patient satisfaction (A Case Study at PuskesmasPagar Dewa, West Lampung). The study employs a quantitative associative approach. The number of respondents in this research is 66 people, in which the entire population is used as the sample through a saturated sampling method. Several statistical tests were conducted, including validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, t-test, and coefficient of determination (R²). The findings indicate that the level of service quality has a positive and significant effect on patient satisfaction. These results highlight the importance of continuously improving service quality not only to maintain existing levels of patient satisfaction but also to enhance public trust in the health center as a reliable and responsive provider of medical services.